2015
DOI: 10.1007/s10895-015-1711-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoluminescence Studies of Eu(III), Er(III) Doped Strontium Gadolinium Tantalum Oxide

Abstract: The luminescence properties of Sr2GdTaO6 have been studied by keeping Eu(3+) as constant concentration and varying Er(3+) concentration. Sr2GdTaO6 phosphor doped with rare earth ions of Eu and Er having monoclinic phase of space group P21/n was synthesized, and their photoluminescence properties have been examined under UV excitation of wavelength 265 nm and 275 nm. PL emission exhibited around 468, 475, 580, 596, and 610 nm wavelength subsequently for various concentrations of Er(3+) for two different excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Several Eu 3+ doped perovskite‐based phosphors have been investigated for their excellent PL display, including Ca 2 YTaO 6 , [ 10 ] Ca 2 GdTaO 6 , [ 11 ] Ca 2 YSbO 6 , [ 12 ] and Sr 2 GdTaO 6 . [ 13 ] This study used a combustion method to synthesize Eu 3+ doped Sr 2 YNbO 6 , which has excellent photoluminescence (PL) and TL properties. As found using a literature survey, only a few papers on optically activated double perovskites doped with Eu 3+ that describe their TL properties have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Several Eu 3+ doped perovskite‐based phosphors have been investigated for their excellent PL display, including Ca 2 YTaO 6 , [ 10 ] Ca 2 GdTaO 6 , [ 11 ] Ca 2 YSbO 6 , [ 12 ] and Sr 2 GdTaO 6 . [ 13 ] This study used a combustion method to synthesize Eu 3+ doped Sr 2 YNbO 6 , which has excellent photoluminescence (PL) and TL properties. As found using a literature survey, only a few papers on optically activated double perovskites doped with Eu 3+ that describe their TL properties have been published.…”
Section: Introductionmentioning
confidence: 99%
“…31 To the best of our knowledge, single Eu 3+ and Er 3+ -doped Sr 2 GdTaO 6 phosphors have been investigated, and Han et al also suggested that Mn 4+ -doped Sr 2 GdTaO 6 phosphors could achieve high quantum yields and good thermal stability via a two-step hightemperature solid-state reaction. 32,33 In this work, we used different raw materials, calcination temperatures and times to prepare the target samples by means of a one-step high-temperature solid-state reaction, which may affect the photoluminescence properties of target products. It is known that the particle size plays a significant role in photoluminescence performances (e.g., emission intensity, quantum yield, and thermal stability).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]. Among all RE 3+ ions, trivalent europium (Eu 3+ ) has been widely investigated for the red emmiting phosphors due to it's characteristic 5 F 0 → 5 I j (J = 0,1,2,3,4) band transitions.…”
Section: Introductionmentioning
confidence: 99%